50MHz auroral doppler radar observations associated with Pc 5 geomagnetic pulsations - Igarashi, Kiyoshi; Ogawa, Tadahiko; Kuratani, Yasukazu; Fujii, Ryoichi; Sato, Natsuo (1985)
P(論文) Radio auroral echo oscillations associated with Pc 5 geomagnetic pulsations are investigated using the 50MHz doppler radar installed in 1982 at Syowa Station, Antarctica. First, it is found that Pc 5 radar echo pulsations occur most frequently around dawn and dusk hours but do not appear around noon and midnight. Then, the doppler power spectrum of the Pc 5 pulsating radio aurora is presented which indicates that the irregularities causing echo pulsations might be produced by the gradient-drift plasma instability in the disturbed E-region. It is also demonstrated by using the mean doppler velocity of the Pc 5 pulsating radio aurora that during the pulsations the north-south components of electric fields are far larger than the east-west components, being consistent with the Kelvin-Helmholtz instability hypothesis as a cause of Pc 5 geomagnetic pulsations. departmental bulletin paper